Governance Analysis of An Electronic-Based Integrated Secretariat Information Management System in Election Supervision - Aldrin A. Christian; Jetty E. H. Mokat; Steven V. Tarore (JR Education, 2026)
This article analyzes the governance of an electronic-based integrated secretariat information management system, known as SIMASTER, in supporting election supervision functions at a provincial election supervisory institution. The study is grounded in the transformation of public administration toward digital governance, where information systems are expected to strengthen efficiency, transparency, accountability, and data-based decision making. A qualitative descriptive approach was used through interviews, observation, and documentation. The analysis focuses on three issues: governance of SIMASTER in supporting the supervisory function, the role of SIMASTER in carrying out election supervisory duties under Law Number 7 of 2017, and the function of SIMASTER in managing election supervision data. The findings show that SIMASTER contributes to faster reporting of alleged violations, better coordination between provincial and local supervisory structures, more systematic documentation, and more transparent monitoring of case progress. However, the system has not yet reached optimal institutional maturity because of uneven technological infrastructure, limited digital literacy among field supervisors, insufficient public outreach, and the need for stronger regulatory and strategic institutionalization. The study argues that the effectiveness of digital election supervision is not determined only by the availability of an application, but also by governance mechanisms, human resource readiness, data validity, interoperability, and public trust. The article recommends strengthening formal governance arrangements, integrating SIMASTER with other electoral systems, improving digital infrastructure in remote areas, providing continuous training, and expanding public communication so that digital election supervision becomes more inclusive, accountable, and sustainable.